Effect of the COVID-19 pandemic on the psychotropic drug consumption - Benistand, Paul; Vorilhon, Philippe; Laporte, Catherine; Bouillon-Minois, Jean-Baptiste; Brousse, Georges; Bagheri, Reza; Ugbolue, Ukadike Chris; Baker, Julien S.; Flaudias, Valentin; Mulliez, Aurélien; Dutheil, Frédéric (Frontiers in Psychiatry, 2022)
Importance: Although the COVID-19 pandemic has had a negative impact on mental health, there is no comprehensive longitudinal study of the entire population of a country without selection bias. Objective: The objective of this study was to evaluate the prescription of psychotropic drugs during the COVID-19 pandemic, using data from the French national health data system (SNDS). Design, settings, and participants: Prescriptions for psychotropic drugs (antidepressants, anxiolytics, hypnotics and antipsychotics) from January 1, 2015 to September 30, 2021 were collected from administrative data provided by the SNDS. This database includes more than 99% of the French population, i.e. 67 million people. The data were analyzed using an interrupted time series analysis (ITSA) model. Main outcomes and measures: Consumption of psychotropic drugs was aggregated in months and expressed in number of boxes per thousand inhabitants. Results: During the study period, more than 1.3 billion boxes of psychotropic medications were dispensed. Comparison of psychotropic drug dispensing before and after the pandemic showed a relative increase of 0.76 (95CI 0.57 to 0.95, p<0.001) boxes per month per thousand inhabitants, all classes of psychotropic drugs combined. Three classes saw their consumption increase in an almost similar proportion, respectively by 0.23 (0.15 to 0.32, p<0.001) boxes for antidepressants, 0.27 (0.20 to 0.34, p<0.001) boxes for anxiolytics and 0.23 (0.17 to 0.30, p<0.001) boxes for hypnotics. The change in antipsychotic consumption was very small, with an increase of 0.04 boxes (0.02 to 0.06, p= 0.001) per month per thousand population. Conclusion and relevance: The COVID-19 pandemic had led to an increase in the consumption of psychotropic drugs, confirming the significant impact of the pandemic on the mental health of the general population.